2005
DOI: 10.1007/s00401-005-1019-3
|View full text |Cite
|
Sign up to set email alerts
|

Redox system expression in the motor neurons in amyotrophic lateral sclerosis (ALS): immunohistochemical studies on sporadic ALS, superoxide dismutase 1 (SOD1)-mutated familial ALS, and SOD1-mutated ALS animal models

Abstract: Peroxiredoxin-ll (Prxll) and glutathione peroxidase-l (GPxl) are regulators of the redox system that is one of the most crucial supporting systems in neurons. This system is an antioxidant enzyme defense system and is synchronously linked to other important cell supporting systems. To clarify the common self-survival mechanism of the residual motor neurons affected by amyotrophic lateral sclerosis (ALS), we examined motor neurons from 40 patients with sporadic ALS (SALS) and 5 patients with superoxide dismutas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
34
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 33 publications
2
34
2
Order By: Relevance
“…Several studies have shown that Prx expression is elevated in neurodegenerative diseases such as AD, Parkinson disease, Creutzfeldt-Jakob disease, and amyotrophic lateral sclerosis (17)(18)(19)(20). However, it is not known if increased Prx expression in these diseases occurs as a general response to nerve cell death or is a protective mechanism elicited by disease-specific stimuli.…”
mentioning
confidence: 95%
“…Several studies have shown that Prx expression is elevated in neurodegenerative diseases such as AD, Parkinson disease, Creutzfeldt-Jakob disease, and amyotrophic lateral sclerosis (17)(18)(19)(20). However, it is not known if increased Prx expression in these diseases occurs as a general response to nerve cell death or is a protective mechanism elicited by disease-specific stimuli.…”
mentioning
confidence: 95%
“…The first symptom of the hSOD1 mice is a fine "jittering/tremor" in one or more of the limbs, which appears at ϳ90 to 100 days of age (21,22). At later stages, the cytopathological features of the hSOD1 transgenic mice include motor neuron loss with astrocytosis, the presence of SOD1-positive inclusions including Lewy body-like hyaline inclusions/astrocyte hyline inclusions, and vacuole formation (23).…”
mentioning
confidence: 99%
“…Finally, an immunohistochemical study of paraffin-embedded spinal cord sections of G1H-G93A mice was performed. The G1H-G93A mice examined at 110 days of age revealed severe loss of anterior horn cells with gliosis and both Lewy body-like hyaline inclusions (LBHIs) and vacuolation pathologies (32). The anti-C111ox-SOD1 selectively labeled the LBHIs in the neuropil and in the cytoplasm of the neurons (Fig.…”
mentioning
confidence: 99%
“…8, B and C). Because the most characteristic neuropathological findings in ALS model mice are LBHIs and vacuoles (32,33), the peroxidation of Cys 111 may contribute to the pathology of the degeneration/ death of FALS motor neurons. However, the amount of the Cys 111 -peroxidized SOD1 appears to be quite limited (Fig.…”
mentioning
confidence: 99%